Про сонячний годинник другої половини XVII ст. на Іллінській церкві при Антонієвих печерах м. Чернігова - Травкіна, О.І. (Сіверщина в історії України, 2021)
У статті висвітлюється питання створення оригінального
сонячного годинника на південному фасаді Іллінської церкви при
Антонієвих печерах у Чернігові у другій половині XVII cт. Порівнявши опис годинника з книги Дмитра Туптала «Руно орошенное» 1696 р. з гравюрою, яка містилася у цьому виданні, авторка
дійшла висновку, що на гравюрі зображено сонячного годинника
з образом Покрови Богородиці, який був створений на стіні Іллінської церкви, але, на жаль, до нашого часу не зберігся. Аналіз
зображення Покрови Богородиці засвідчив, що його автором був
митець, обізнаний з європейським мистецтвом, оскільки іконографічний варіант Богородиці Покрови належав до європейського
типу «Misericordia». Висувається гіпотеза, що до створення неординарного сонячного годинника із зображенням Покрови Богородиці могли бути причетними ігумен Троїцько-Іллінського монастиря
Лаврентій Крщонович та відомий гравер Інокентій Щирський. Ці
митці мали високу освіту, навчалися друкарству та гравіюванню
у Вільно (столиця Великого князівства Литовського), видавали й
оформлювали книги. Факт створення неординарного, оригінального годинника, аналогій якому не було у Гетьманщині, засвідчив,
що Чернігів був неабияким культурним осередком Північного Лівобережжя України, в якому активно розповсюджувалися мистецькі твори, позначені європейськими впливами. The article covers the issue of creating an original sundial on the southern
facade of the Church of St. Elias at the Anthoniy’s Caves in Chernihiv
in the second half of the XVII century. Comparing the description
of the clock from Dmytro Tuptal’s book «Irrigated Fleece» in 1696 with
the engraving contained in this edition, the author concluded that the
engraving depicts a sundial with the image of the Intercession of the Virgin,
which was created on the wall of St. Elias’ Church, but unfortunately. The
analysis of the image of the Intercession of the Virgin Mary showed that
its author was an artist familiar with European art, as the iconographic
version of the Intercession of the Virgin Mary belonged to the European
type «Misericordia». The appearance of such a sundial with the image of
the Intercession of the Virgin in Chernihiv was not accidental. Thanks to
the activities of the Archbishop of Chernihiv Lazar Baranovych, who as a
vicar of the Kyiv metropolis, lived in Chernihiv from 1672 and together with
hetmans, Cossack sergeants restored and built churches, engaged in literary
work, printed books, involved talented writers in the work of Chernihiv. It
is hypothesized that the abbot of the Trinity-Elias Monastery Lavrentiy
Krshchonovych and the famous engraver Inokentiy Shchyrsky may have
been involved in the creation of an extraordinary sundial with the image of
the Intercession of the Mother of God. These artists were highly educated,
studied printing and engraving in Vilno (the capital of the Grand Duchy
of Lithuania), and published and designed books. The fact of creating an
extraordinary, original clock, which had no analogies in the Hetmanate,
showed that Chernihiv was a remarkable cultural center of the Northern
Left Bank of Ukraine, which actively distributed works of art marked by European influences.